(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
This study assessed horizontal and vertical distribution and abundance of zooplankton community in water samples collected from 26 stations at a depth of 0 to 250 m of the northern Bay of Bengal. A total of 55 zooplankton species were identified where Copepod was 72.41% and Ciliophora was 8.62%. Among the Copepod, 48%, 40% and 12% of species were Calanoid, Cyclopoid and Harpacticoid Copepod, respectively. This study also found 2 species of Decapod, 2 species of Rotifer, 2 species of Cladocera, 1 species of Chaetognatha and 1 species of Stomatopoda. Spatial distribution of zooplankton species was varied from station to station and cruise to cruise. Maximum 23,868 individuals of zooplanktons were recorded in cruise 2, whereas the lowest number (758 individuals) was found in cruise 4. Zooplankton abundance was ranged between 18 to 22,500 cells/L in all cruises, whereas the highest abundance was found in cruise 2 and the lowest was recorded in cruise 4. The highest abundance (37,310 individuals) was documented at surface water and the lowermost number of zooplankton (10 individuals) was recorded at 100 m depth. This study showed negative correlation between zooplankton abundance and water depth. The results of the current study might help to understand zooplankton abundance and distribution in the northern Bay of Bengal and will use as a baseline study for further research. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(2), 2021, P 1-8